"Train how you play": Using representative learning design to train amateur cricketers. Issue 5 (4th March 2022) - Lascu, Alexandra; Spratford, Wayne; Pyne, David B.; Etxebarria, Naroa
ABSTRACT: Training task design with amateur female cricketers has typically comprised of deconstructed and monotonous approaches which may not maximise skill development. Clear guidelines to improve these practices in this cohort are lacking. The training environment should provide the same sources of information, decisions and variability as matches in order to prepare players for the match environment, which can be achieved through representative learning design (RLD). An RLD training intervention designed to promote skill development was performed over five weeks with two amateur female cricket teams to provide a framework for community coaches at the foundation stage of cricket. Skill development was recorded as changes in skilled actions for batting and bowling, with cognitions coded as themes for each skill during training. Six of ten batters and seven of eight bowlers exhibited increases in skill development ranging between 7–49%. Changes in batting and bowling behaviour improved substantially between moderately and extensively designed sessions. Batters' thoughts shifted from their own skill execution to objectives, while bowlers focused on their opponent's execution. Moderate to extensive RLD appears to promote skill development in amateur cricketers, making it a viable option for coach education and training design at the foundation level of cricket.